Aqueous photodegradation of the benzophenone fungicide metrafenone: Carbon-bromine bond cleavage mechanism. (1st November 2021) - Hong, Minghui; Yang, Xuerui; Zhang, Xuewei; Ji, Yuefei; Zhou, Lei; Xiu, Guangli; Ni, Zhigang; Richard, Claire
Highlights: MF underwent relatively rapid direct photodegradation under simulated sunlight. Debromination was identified as the primary photolysis path of MF. Homolytic C-Br cleavage mechanism was verified by LFP technique and DFT calculation. The bond dissociation energy value (C-Br) was obtained by DFT calculation. Abstract: Metrafenone (MF), as a new type of benzophenone fungicide, has been widely used in agriculture and is persistent in the environment. Understanding its photochemical fate is essential for the comprehensive evaluation of its ecological risk. In the present work, we reported a detailed study on the photochemical transformation of MF in aqueous solution under irradiation (at λ > 290 nm using a high pressure mercury lamp). MF was relatively photo-reactive showing a low polychromatic quantum yield of photolysis (1.06 × 10 −4, 20 µM) counterbalanced by a significant light absorption above 290 nm. A series of photoproducts were identified by high resolution mass spectrometry (HR-MS) analysis, and three different pathways, including oxidation of the methyl group, debromination and replacement of bromine by hydroxyl group were proposed. Among them, debromination was identified as the dominating process that could be achieved via homolytic C-Br bond cleavage from singlet and triplet MF, as confirmed by laser flash photolysis (LFP) experiments and density functional theory (DFT) calculations. Toxicity assessment revealed that photochemical degradation reduced the ecotoxicity of MF efficiently. Nitrate ions and humic acid promoted the MF photolysis, while bicarbonate exhibited no effect. Results obtained in this work would increase our understanding on the environmental fate of MF in sunlit surface waters. Graphical abstract: Image, graphical abstract